Exploring Senior High School Students’ English Learning Demotivation in Mainland China - Gao, Lixiang; Liu, Honggang; Liu, Xiaoxi (Frontiers in Psychology, 2022)
In the last 20 years, much attention has been paid to learners’ demotivation. Researchers have conducted many studies on second/foreign language learning demotivation from the perspectives of social culture, social psychology, and so forth. In China, related studies have mainly focused on college students’ demotivation; scant attention has been paid to senior high school students. Regarding scale development, although much progress has been made, there remains a need for a scale with high reliability and validity that is suitable for students in the basic education stage. Therefore, based on previous studies and choosing Chinese senior high school students as participants, this research study developed a scale with 55 items, and exploratory factor analysis was used to develop a 28-item scale with six dimensions. The six-dimensional construct encompasses teacher knowledge, important others, teacher responsibility, learner-related factors, learning contents, and critical incidents, which are the key factors leading to English learners’ demotivation. Among them, the factor of critical incidents is new and has been overlooked by other researchers. Moreover, the descriptive analysis demonstrated the degree to which the demotivators influence learners, and the independent sample t-test found a significant difference in the impact of critical incidents in terms of the students’ language proficiency. Ultimately, three suggestions are put forward to remotivate and sustain learners’ motivation.